Identify Causes Students Against Misconceptions in SMA Biology Material As Langsa - Nurul Fadillah (Jurnal Pendidikan Biologi, 2018)
Misconception is the notion of a concept that is not right, wrong in using the concept of the name, one of the concepts classify examples, doubts about the different  concepts,  not  right  in  connecting  a  wide  range  of  concepts  in  the hierarchy composition or manufacture of a generalization of the concept of excessive or less clear. This study aims to determine how much misconceptions and identify the factors that cause misconceptions students of class XI against biological materials in SMA as Langsa. This research was conducted in SMA as Langsa. The population in this study were all students of class XI Science SMAN as  Langsa.  Sampling  technique  in  this  study  conducted  stratified  random sampling, so the sample used was 210 students. This study used research instrument in the form of two-dimensional diagnostic tests, questionnaires and interviews. The results showed that the percentage of students' misconceptions of the material in high school biology class XI as Langsa State is 21%. The factors that cause student misconceptions that book 24.90%, 3.34% teachers,  parents 0.83%, 12.80% friends, internet 1.63%, 0.10% beliefs, and others that students responded by reading the student worksheet (LKS) or by believing in yourself by 56.39%.